Comparison of Three Daily Rainfall-Runoff Hydrological Models Using Four Evapotranspiration Models in Four Small Forested Watersheds with Different Land Cover in South-Central Chile - Neftali Flores; Rolando Rodríguez; Santiago Yépez; Victor Osores; Pedro Rau; RIVERA SALAZAR, DIEGO ANDRÉS; Francisco Balocchi (My University, 2021)
We used the lumped rainfall–runoff hydrologic models Génie Rural à 4, 5, 6 paramètres Journalier (GR4J, GR5J and GR6J) to evaluate the most robust model for simulating discharge on four forested small catchments (<40 ha) in south-central Chile. Different evapotranspiration methods were evaluated: Oudin, Hargreaves–Samani and Priestley–Taylor. Oudin’s model allows the achievement of the highest efficiencies in the flow simulation. The more sensitive parameters for each model were identified through a Generalized Probability Uncertainty Estimation (GLUE) model. Our results demonstrate that the three hydrological models were capable of efficiently simulating flow in the four study catchments. However, the GR6J model obtained the most satisfactory results in terms of simulated to measured streamflow closeness. In general, the three models tended to underestimate peak flow, as well as underestimate and overestimate flow events in most of the in situ observations, according to the probability of non-exceedance. We also evaluated the models’ performance in a simulation of summer discharge due to the importance of downstream water supply in the months of greatest scarcity. Again, we found that GR6J obtained the most efficient simulations.
Keywords: hydrological models; small catchment; plantations; pinus radiata; nothofagus glauca; eucalyptus nitens; chile; eucalyptus nitens; nothofagus glauca; pinus radiata; catchments; evapotranspiration; forestry; rain; water supply; central chile; daily rainfall; eucalyptus nitens; hydrological models; nothofagi glauca; nothofagus; pinus radiata; plantation; rainfall runoff; small catchment; evapotranspiration; forested catchment; hydrological modeling; land cover; rainfall-runoff modeling; simulation; streamflow; watershed; runoff